The Marginal Cost of Public Funds - Browning, Edgar K. (Journal of Political Economy, 1976)
The marginal cost of public funds is the direct tax burden plus the marginal welfare cost produced in acquiring the tax revenue. This paper estimates that the marginal cost of public funds for taxes on labor income in the United States ranges from 1.09 to 1.16 per dollar of tax revenue, depending on the progressivity of the change in the tax structure. Thus, government expenditures must be at least 9-16 percent more productive than private expenditures to produce a net welfare gain. In addition, the total welfare cost of income taxes in 1974 is estimated at $19 billion.